2010
DOI: 10.5194/cpd-6-1163-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clouds and the Faint Young Sun Paradox

Abstract: We investigate the role which clouds could play in resolving the Faint Young Sun Paradox (FYSP). Lower solar luminosity in the past means that less energy was absorbed on Earth (a forcing of -50 W m<sup>−2</sup> during the late Archean), but geological evidence points to the Earth being at least as warm as it is today, with only very occasional glaciations. We perform radiative calculations on a single global mean atmospheric column. We select a nominal set of three layered, randomly overlappi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 78 publications
5
48
0
Order By: Relevance
“…On the other hand, hazes can also act as cloud condensation nuclei, enhancing cloud formation (Hasenkopf et al , 2011). This might lead to cooling of the planet or even warming depending on cloud particle size and the altitude—and therefore temperature—of the cloud layer (Goldblatt and Zahnle, 2011). A complete treatment of the impact of ice-albedo feedback, haze deposition, haze circulation, and cloud feedbacks is left to future General Circulation Model (GCM) studies better equipped to deal with these inherently 3-D issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hazes can also act as cloud condensation nuclei, enhancing cloud formation (Hasenkopf et al , 2011). This might lead to cooling of the planet or even warming depending on cloud particle size and the altitude—and therefore temperature—of the cloud layer (Goldblatt and Zahnle, 2011). A complete treatment of the impact of ice-albedo feedback, haze deposition, haze circulation, and cloud feedbacks is left to future General Circulation Model (GCM) studies better equipped to deal with these inherently 3-D issues.…”
Section: Resultsmentioning
confidence: 99%
“…This includes the effect of clouds, which is standard in this 1-D treatment (Kopparapu et al , 2013) and is the albedo that reproduces the average temperature of present-day Earth (288 K) with modern atmospheric conditions. Of course, the true cloud distribution on Archean Earth is unknown, and clouds may have had important climatic effects on our early planet (Goldblatt and Zahnle, 2011). The solar zenith angles (SZAs) used in the climate and photochemical models were chosen to best represent globally averaged behavior of the physics in each specific model, which Segura et al (2003) found as SZA = 45° in the photochemical model and SZA = 60° in the climate model.…”
Section: Models and Methodsmentioning
confidence: 99%
“…Clouds play a key role in the climates of Earth, past and present (Goldblatt & Zahnle 2010;Hartmann et al 1986) and Venus (Titov et al 2007). However, their effects are extremely hard to predict in general, due to continued uncertainty in microphysical and small-scale convective processes.…”
Section: Sensitivity Of the Results To Cloud Assumptionsmentioning
confidence: 99%
“…Surface albedo in this model is therefore considered as a tunable parameter that is adjusted in order to allow the model to reproduce an Earth-like climate under present-day conditions. This approach, as well as possible alternatives, have been discussed (Goldblatt & Zahnle 2010;Rondanelli & Lindzen 2010), but three dimensional general circulation models are ultimately required to properly constrain the effects of partial cloud cover.…”
Section: Methods: Energy Balance Model For Early Marsmentioning
confidence: 99%